2000
DOI: 10.1191/096120300678828046
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in three ethnic groups. VI: Factors associated with fatigue within 5 years of criteria diagnosis

Abstract: Fatigue is one of the most prevalent clinical manifestations of SLE across all ethnic groups. The perception of fatigue severity in SLE may be multifactorial in origin, including psychosocial factors and disease activity. If these prove causal, knowledge of their contribution may suggest therapeutic and/or behavioral interventions, which could ameliorate this pervasive and often incapacitating symptom of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
138
1
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(159 citation statements)
references
References 32 publications
13
138
1
7
Order By: Relevance
“…The Fatigue Severity Scale has been used to subjectively evaluate fatigue in SLE and other chronic conditions (1,4,19,20). Previous studies reported FSS in patients with SLE ranging from 4.6 to 5.3 (1,19). These scores were similar to the scores of patients with mild SLE in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The Fatigue Severity Scale has been used to subjectively evaluate fatigue in SLE and other chronic conditions (1,4,19,20). Previous studies reported FSS in patients with SLE ranging from 4.6 to 5.3 (1,19). These scores were similar to the scores of patients with mild SLE in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the LUMINA cohort has been published previously (23)(24)(25)(26)(27)(28). We are therefore describing only the salient baseline features for the LUMINA patients included in these analyses (72 Hispanics, 104 African Americans, and 82 Caucasians).…”
Section: Resultsmentioning
confidence: 99%
“…The constitution of this cohort, the variables obtained prior to, at, and after enrollment in the cohort, and the frequency and nature of the study visits have been described in detail previously (23)(24)(25)(26)(27)(28). Briefly, patients with SLE according to the American College of Rheumatology (ACR) criteria (4,29,30) who had disease duration of Յ5 years at enrollment, were living within the catchment area of the participating institutions (The University of Alabama at Birmingham, The University of Texas-Houston Health Science Center, and The University of Texas Medical Branch at Galveston), and were of defined Hispanic (Mexican American or Central American), African American, or Caucasian ethnicity were eligible to participate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vários factores são reconhecidos como contribuintes para a fadiga, como a actividade da doença, desordens de humor, padrões de sono inadequados, forma física aeróbica debilitada e presença de fibromialgia (Krupp, 1990;Tench et al, 2000;Wy-senbeek et al, 1993;Zonana-Nacach et al, 2000). A relação entre a fadiga e a actividade da doença é controversa.…”
unclassified